2010
DOI: 10.1007/s10528-009-9325-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Diversity of Orchid Bee Euglossa fimbriata (Hymenoptera: Apidae) Populations Assessed by PCR-RFLP

Abstract: Euglossa fimbriata is a euglossine species widely distributed in Brazil and occurring primarily in Atlantic Forest remnants. In this study, the genetic mitochondrial structure of E. fimbriata from six Atlantic Forest fragments was studied by RFLP analysis of three PCR-amplified mtDNA gene segments (16S, COI-COII, and cyt b). Ten composite haplotypes were identified, six of which were exclusive and represented singleton mitotypes. Low haplotype diversity (0.085-0.289) and nucleotide diversity (0.000-0.002) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Total DNA was extracted from the muscle tissues of A. gemmatalis samples following the protocol, with modifications [29] and purified with 7.5 M ammonium acetate and 70% and 100% ethanol. The concentration and purity of the DNA was determined in NanoDrop™ and the samples were diluted to concentrations of 100 ng/μl for the procedures that follow.…”
Section: Isolation Of 18s Rdna and Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…Total DNA was extracted from the muscle tissues of A. gemmatalis samples following the protocol, with modifications [29] and purified with 7.5 M ammonium acetate and 70% and 100% ethanol. The concentration and purity of the DNA was determined in NanoDrop™ and the samples were diluted to concentrations of 100 ng/μl for the procedures that follow.…”
Section: Isolation Of 18s Rdna and Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…Relatively few genetic studies have investigated bee species within other genera, such as Plebeia remota (Francisco et al, 2001), Eufrisea violacea (Sofia et al, 2005), Macrotera portalis (Danforth et al, 2003), Tetragonisca angustula (Oliveira et al, 2004), Partamona helleri (Brito and Arias, 2010), Partamona seridoensis (Fernandes et al, 2012), Melipona subnitida (Cruz et al, 2006), and Euglossa fimbriata (Suzuki et al, 2010). Some of these studies have used PCR-RFLP (Francisco and Arias, 2010;Brito and Arias, 2010;Suzuki et al, 2010) revealing interesting information that has allowed researchers to distinguish populations.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have used PCR-RFLP (Francisco and Arias, 2010;Brito and Arias, 2010;Suzuki et al, 2010) revealing interesting information that has allowed researchers to distinguish populations. The COI/COII mitochondrial DNA region is known to be highly variable in Apis mellifera (Garnery et al, 1993;Franck et al, 1998) and stingless bees (Francisco et al, 2001;Fernandes-Salomão et al, 2002;Weinlich et al, 2004;Moretto and Arias, 2005;Brito and Arias, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their importance in the maintenance of gene flow across Neotropical forests, a number of studies have suggested that euglossine bees are sensitive to forest fragmentation and a reduction in the size of forest fragments (Powell and Powell 1987;Sofia and Suzuki 2004;Brosi et al 2008;Brosi 2009). On the other hand, genetic studies involving different orchid bee species have shown that even in fragmented landscape scenarios, some species have maintained high levels of population genetic diversity (Sofia et al 2005;Suzuki et al 2010;Cerântola et al 2011;Zimmermann et al 2011).…”
Section: Introductionmentioning
confidence: 99%